Candidate Gene Markers Associated with Fecal Shedding of the Feline Enteric Coronavirus (FECV) - Bubenikova, Jana; Vrábelová, Jana; Stejskalova, Karla; Futas, Jan; Plasil, Martin; Cerna, Petra; Oppelt, Jan; Lobova, Dana; Molinkova, Dobromila; Horin, Petr (Pathogens, 2020)
The Feline coronavirus (FCoV) can cause a fatal disease, the Feline Infectious Peritonitis. Persistent shedders represent the most important source of infection. The role of the host in FCoV fecal shedding is unknown. The objective of this study was to develop gene markers and to test their associations with FCoV shedding patterns. Fecal samples were taken from 57 cats of 12 breeds on the day 0 and after 2, 4 and 12 months. Variation from persistent and/or high-intensity shedding to no shedding was observed. Thirteen immunity-related genes were selected as functional and positional/functional candidates. Positional candidates were selected in a candidate region detected by a GWAS analysis. Tens to hundreds of single nucleotide polymorphisms (SNPs) per gene were identified using next generation sequencing. Associations with different phenotypes were assessed by chi-square and Fisher's exact tests. SNPs of one functional and one positional candidate (NCR1 and SLX4IP, respectively) and haplotypes of four genes (SNX5, NCR2, SLX4IP, NCR1) were associated with FCoV shedding at pcorected < 0.01. Highly significant associations were observed for extreme phenotypes (persistent/high-intensity shedders and non-shedders) suggesting that there are two major phenotypes associated with different genotypes, highly susceptible cats permanently shedding high amounts of viral particles and resistant non-shedders.